Accelerating drug discovery with machine learning and AI - Isayev, Olexandr (Henry Stewart Talks, 2022)
Machine-learning techniques, Artificial intelligence methods, Drug discovery, Molecular modeling, Choosing a disease, Identifying a drug target, Choosing the bioassay, AlphaFold 2: Protein structure prediction, Computer-assisted drug design, NIH IDG-DREAM, Predictive vs. generative models, Molecular design with deep reinforcement learning
Reviewed at 2024/05/19